(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rahmi Z, Yurnaliza Y, Hastuti LDS. 2022. Isolation and screening of lovastatin-producing endophytic fungi from lemongrass (Cymbopogon nardus L.). Biodiversitas 23: 4189-4194. Fungi have long been studied for their cholesterol-lowering compounds, known as statins and the derivatives through fermentation in laboratory investigations. Therefore, this study aimed to isolate and screen endophytic fungal strains from lemongrass capable of producing lovastatin. Endophytic fungi were isolated from the stems and leaves of lemongrass (Cymbopogon nardus) and the selection of their ability to produce lovastatin was assayed using three approaches, namely negative test against Candida albicans, measurement based on absorbance at a wavelength (?) of 230 nm or colorimetric assay, and observation using thin layer chromatography (TLC). A total of 22 endophytic fungi, 15 from the leaves and 7 from the stems were isolated from lemongrass. The capability to produce lovastatin was confirmed using three approaches, resulting in three potential fungal strains, namely Trichoderma sp. CNB 2.5.3, unidentified fungus CND 2.5.4, and Nigrospora sp. CND 2.1.1. Based on the colorimetric assay, the potential strains produced a significant zone of inhibition against C. albicans, with greater lovastatin levels than the other isolates. The TLC analysis showed that the fungal ethanolic extracts contained crude lovastatin as indicated from the same retention factor (Rf) value as standard lovastatin. The presence of lovastatin-producing endophytic fungi can be investigated progressively for optimum production through fermentation and evaluation of its cholesterol-lowering activity in the future.